2021
DOI: 10.1158/1078-0432.ccr-20-3210
|View full text |Cite
|
Sign up to set email alerts
|

A MET Targeting Antibody–Drug Conjugate Overcomes Gemcitabine Resistance in Pancreatic Cancer

Abstract: Purpose: Pancreatic cancer is an aggressive disease associated with a poor 5-year overall survival. Most patients are ineligible for surgery due to late diagnosis and are treated primarily with chemotherapy with very limited success. Pancreatic cancer is relatively insensitive to chemotherapy due to multiple factors, including reduced bioavailability of drugs to tumor cells. One strategy to improve drug efficacy with reduced toxicity is the development of antibody-drug conjugates (ADC), which have now been use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…successfully designed an antibody‐drug conjugate (TR1801‐ADC) that enhanced the tumor inhibition (in vitro and in vivo) in Met overexpressed pancreatic cancer and worked in synergy with gemcitabine. [ 78 ] CSCs are one of the leading players of PDAC distal metastasis. Hermann et al.…”
Section: Challenges Of Pdac Treatmentmentioning
confidence: 99%
“…successfully designed an antibody‐drug conjugate (TR1801‐ADC) that enhanced the tumor inhibition (in vitro and in vivo) in Met overexpressed pancreatic cancer and worked in synergy with gemcitabine. [ 78 ] CSCs are one of the leading players of PDAC distal metastasis. Hermann et al.…”
Section: Challenges Of Pdac Treatmentmentioning
confidence: 99%
“…To facilitate application, five DDR- and immune-based genes were finally selected and DPRS was subsequently constructed. Studies have consistently shown that MET overexpression is a negative prognostic indicator in a variety of malignancies, and activation of the HGF-MET axis was associated with the drug resistance of tumor cells [ 18 , 19 , 20 ]. In this study, MET was significantly negatively correlated with CD8+ T cells, CD4+ T memory activated cells, plasma cells and naïve B cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent preclinical study has identified signaling by the hepatocyte growth factor receptor MET as a potential driver of Gemcitabine resistance in PDAC. In this work, the authors show that MET is highly expressed at the plasma membrane of pancreatic cancer cells, and that TR1801-ADC, a novel antibody drug conjugate composed of a MET antibody conjugated to the highly potent pyrrolobenzodiazepine toxin-linker Tesirin was highly effective in MET-overexpressing patient derived xenografts, and synergized with Gemcitabine, even in tumors previously demonstrated to be resistant to Gemcitabine (183). Hence, these and other combination strategies warrant continued exploration in the treatment of Gemcitabine-refractory PDAC.…”
Section: Strategies To Overcome Gemcitabine Resistancementioning
confidence: 96%